How Do People in Animal Welfare Fields Respond to Family Violence Situations? - Poe, Bethanie Allison (2016)
Cross-reporting refers to the idea that people working in human welfare and people in animal welfare fields who observe or have suspicions of abuse or neglect of children, domestic violence, elderly or disabled people, or animals, respectively, are obligated to report their observations to the appropriate agencies. This exploratory study investigates the types of maltreatment witnessed or observed while at work by people in animal related fields; what responses these workers are making to what they are seeing; and the factors influencing their responses. Using an open online survey, this study found that 21% to 29% of the participants indicated that at some point in the last 12 months they have found themselves in situations at work where they were concerned about the safety or well-being of a child, potential domestic violence, or about an elderly and/or disabled adult. For children and vulnerable adults, warning signs of neglect were the most common reason for concern, while something a partner said or threats most often prompted concerns about intimate partner violence. A lack of evidence, the severity of the situation, and agency/organizational policy were the most commonly cited influencing factors respondents reported across situations. Forty-eight percent of participants (n = 202) indicated that their organization has policies regarding making reports to other agencies such as law enforcement, child protective services, or adult protective services While the current study has substantial limitations—including sample size, unrepresentativeness and the lack of generalizability of the sample, as well as selection and recall bias-- it provides a first glimpse of the state of cross-reporting from the perspective of people in animal related fields. Further research is needed that focuses on specific professions within animal welfare, captures a more nuanced picture of people’s responses to maltreatment, and looks more closely at the impact of training and agency policy